Study of Air Conditioning System (HVAC) Design for Mall XYZ: Studi Perancangan Sistem Pengkondisian Udara (HVAC) Mall XYZ - Sinaga, Franklin Taruyun Hudeardo; Nisfan Bahri, Nisfan Bahri; Al Qadry (Atech-i, 2025)
Air conditioning systems are crucial for achieving optimal thermal comfort and air quality incommercial environments such as shopping malls. This research focuses on redesigning the airconditioning system at XYZ Mall in Serpong, Tangerang, with the primary goal of identifyingpotential energy savings. The design involved calculating the cooling load, selecting keycomponents such as the Air Handling Unit (AHU) and chiller, and determining the piping andducting system. The calculations indicate that the total cooling load at XYZ Mall is 1,082.54 TR.Although the existing installation is theoretically designed to minimize energy consumption, fieldobservations indicate opportunities for further savings through optimizing chiller operation.Keywords: Air Conditioning Systems, Cooling Loads, AHUs, Chillers, Energy Efficiency.